Ncd motor binding and transport in the spindle. - Hallen, M.A.; Liang, Z.Y.; Endow, S.A. (Journal of Cell Science, 2008)
The Ncd kinesin-14 motor is required for meiotic spindle assembly in Drosophila oocytes and produces force in mitotic spindles that opposes other motors. Despite extensive studies, the way the motor binds to the spindle to perform its functions is not well understood. By analyzing Ncd deleted for the conserved head or the positively charged tail, we found that the tail is essential for binding to spindles and centrosomes, but both the head and tail are needed for normal spindle assembly and function. Fluorescence photobleaching assays to analyze binding interactions with the spindle yielded data for headless and full-length Ncd that did not fit well to previous recovery models. We report a new model that accounts for Ncd transport towards the equator revealed by fluorescence flow analysis of early mitotic spindles and gives rate constants that confirm the dominant role the Ncd tail plays in binding to the spindle. By contrast, the head binds weakly to spindles based on analysis of the tailless fluorescence recovery data. Minus-end Ncd thus binds tightly to spindles and is transported in early metaphase towards microtubule plus-ends, the opposite direction to that in which the motor moves, to produce force in the spindle later in mitosis.